Вплив парціального тиску азоту на реактивне магнетронне розпилення Ti13Cu87 мішені: моделювання хімічного складу - Rahmati, A.; Khanzadeh, M. (Publishing house "Academperiodika", 2012)
A sintered Ti13Cu87 composite target was reactively sputtered in Ar–N2 gas mixtures, and sputtered species were deposited on Si (111) substrates. We study the pressure-dependent target mode variation of the Ti13Cu87–N2 system, by measuring the N2 partial pressure, deposition rate, target voltage, and Ti and Cu concentrations for various reactive N2 gas flow ratios. The Ti13Cu87 target surface begins to be nitrided with increasing N2 flow ratio, which is caused by the absorption and the implantation of N2 gas on the Ti13Cu87 target surface. Hence, the deposition rate was reduced due to the lower sputtering yield and a higher scattering under the mass transport between the target-substrate spacing. Secondary electron emission yield of the nitride portion of targetsurface is higher than that of the unnitrided portion. Therefore, at a constant sputtering power, the target voltage decreases, as the N2 partial pressure increases. By means of the TRIM.SP Monte-Carlo simulation, the particle reflection coefficients of reflected neutrals was calculated. The initial energies of reflected neutrals and the sputtered particles at the substrate were estimated using the simple binary collision model and the distribution-weighted averages, respectively. Their final energies depend on the energy dissipation during the mass transport through the gas phase. The energy and angular characteristics of the sputtering yield were extracted from the available literature to obtain a prediction about a final composition of films.